2020
DOI: 10.1108/ijccsm-06-2019-0037
|View full text |Cite
|
Sign up to set email alerts
|

Climate change: vegetation and phenological phase dynamics

Abstract: Purpose The ecological environment of the Loess Plateau, China, is extremely fragile under the context of global warming. Over the past two decades, the vegetation of the Loess Plateau has undergone great changes. This paper aims to clarify the response mechanisms of vegetation to climate change, to provide support for the restoration and environmental treatment of vegetation on the Loess Plateau. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…Specifically, lower TV % (about 1 %) correspond to forests placed at lower altitudes, suggesting that climate change determine stronger effects on forests located at higher altitudes (about 4 %). Results seem to be consistent with a recent studies [74,[77][78][79] that found that vegetation greening and climate warming effects trends were stronger at higher altitudes, thus supporting the idea that an altitudinal gradient effect operates in determining forests vigor level and changes. Conversely, pastures showed a negative altitudinal TV% gradient.…”
Section: Forests Az1supporting
confidence: 91%
“…Specifically, lower TV % (about 1 %) correspond to forests placed at lower altitudes, suggesting that climate change determine stronger effects on forests located at higher altitudes (about 4 %). Results seem to be consistent with a recent studies [74,[77][78][79] that found that vegetation greening and climate warming effects trends were stronger at higher altitudes, thus supporting the idea that an altitudinal gradient effect operates in determining forests vigor level and changes. Conversely, pastures showed a negative altitudinal TV% gradient.…”
Section: Forests Az1supporting
confidence: 91%
“…Therefore, before extracting the vegetation phenology parameters, one needed to smooth the EVI time-series data to further remove the effects of noise. Relevant studies [50,51] have confirmed that the Savitzky-Golay filtering method performs best in most situations when de-noising time-series vegetation index data from various satellite sensors. Therefore, the EVI time-series were reconstructed using the Savitzky-Golay method here.…”
Section: Data Smoothing and Phenology Extractionmentioning
confidence: 95%
“…The spatial patterns of the multi-year average SOS and EOS in this study were consistent with the results of most scholars [43,[68][69][70], but EOS was slightly different from their results in the size of the value. Studies by many scholars [51,71,72] have shown that the SOS of vegetation in the LP tends to advance, EOS tends to delay, and the growing season becomes longer. As a result, the differences and variations in phenological parameters may lead to the deviations in WVCI to a certain extent.…”
Section: Factors Affecting Wvci Performancementioning
confidence: 99%
“…However, there is an ongoing discussion among scholars regarding the extent to which human activities contribute to vegetation greening on the Loess Plateau [38][39][40]. Most research has focused on vegetation greenness at the regional [38,[41][42][43][44][45] or watershed scale [46][47][48][49][50], with limited studies conducted at the county scale. Additionally, the analysis of driving factors behind spatiotemporal changes in vegetation greenness has mainly focused on natural factors [51][52][53], with limited consideration of socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%